Local Administration of Interleukin-1 Receptor Antagonist Improves Diabetic Wound Healing. (May 2018) - Perrault, David P.; Bramos, Athanasios; Xu, Xingtian; Shi, Songtao; Wong, Alex K.
Abstract : Abstract: Impaired healing of the skin is a notable cause of patient morbidity and mortality. In diabetic individuals, dysregulated inflammation contributes to delayed wound healing. Specific immunomodulatory agents may have a role in the treatment of diabetic wounds. One of these molecules is interleukin-1 receptor antagonist (Anakinra; Amgen Corp.). Although interleukin-1 receptor antagonist (Anakinra; Amgen Corp.) is approved by the Food and Drug Administration (FDA) for the treatment of rheumatoid arthritis and neonatal-onset multisystem inflammatory disease, little is known about the local use this drug in cutaneous wound healing. Therefore, the aim of this study is to determine the effect of locally administered interleukin-1 receptor antagonist on delayed wound healing, specifically, in a diabetic mouse model. Two 6-mm full-thickness wounds were created on the dorsa of diabetic (db/db) mice and stented. One-hour postwounding, wound margins were subcutaneously injected with either (1) low-dose interleukin-1 receptor antagonist in a gelatin-transglutaminase gel vehicle or (2) the gel vehicle only. Wounds were imaged on days 0, 7, 14, and 21 postwounding, and wound area was determined. Wound biopsies were collected on day 21 and immunohistochemically stained for neutrophil and macrophage infiltration. Wounds treated with interleukin-1 receptor antagonist had significantly smaller wound area than nontreated wounds on day 7 and day 14 postwounding. Treated wounds also showed significantly less neutrophil and macrophage infiltration. These findings support the hypothesis that interleukin-1 receptor antagonist may have an important role in cutaneous wound healing, possibly by promoting successful resolution of acute inflammation and hence accelerating wound closure. Thereby, administration of IL-1Ra may be useful in the treatment of nonhealing wounds.